Antibiotic intervention redisposes bacterial interspecific interacting dynamics in competitive environments. (24th March 2021) - Li, Jing; Chen, Xiaojie; Lin, Jiafu; Yuan, Yang; Huang, Ting; Du, Lianming; Prithiviraj, Balakrishnan; Zhang, Aixue; Wang, Xinrong; Chu, Yiwen; Zhao, Kelei
Summary: Interspecific interaction happens frequently among bacterial species and can promote the colonization of polymicrobial community in various environments. However, it is not clear whether the intervention of antibiotics, which is a common therapeutic method for infectious disease, will influence the interacting dynamics of different pathogenic bacteria. By using the frequently co‐isolated bacteria Pseudomonas aeruginosa and Staphylococcus aureus as models, here we identify an antibiotic‐determined mutual invasion relationship between bacterial pathogens. We show that although P . aeruginosa has a significant intrinsic competitive advantage over S . aureus by producing the quorum‐sensing (QS)‐controlled anti‐staphylococcal molecules, methicillin‐resistant S . aureus (MRSA) can inhibit neighbouring P . aeruginosa in the presence of subinhibitory aminoglycoside antibiotics (e.g. streptomycin) to P . aeruginosa . Importantly, subinhibitory streptomycin decreases the expression of QS‐regulated genes in P . aeruginosa and thus relieves the survival stress of MRSA brought by P . aeruginosa . On the other side, the iron‐uptake systems and pathogenicity of MRSA can be enhanced by the extracellular products of streptomycin‐treated P . aeruginosa . Therefore, this study provides an explanation for the substitution of dominant species and persistent coexistence of bacterial pathogens in the host with repeated antibiotic therapies and contributes to further understanding the pathogenesis of chronic polymicrobial infections.